Identification of a T-cell epitope on the circumsporozoite protein of Plasmodium vivax. - George, F W (1990)
A series of overlapping peptides, representing sequences in the vicinity of region II on the Plasmodium vivax circumsporozoite protein, was synthesized. One of the peptides (PV-23), a 20-mer containing the 6 C-terminal amino acids of region II, was found to evoke an in vitro T-cell proliferative response in spleen cells from C3Hf (H-2km2) mice immunized with the peptide. These results demonstrate that PV-23 contains a T-cell epitope. To our knowledge, this is the first report of a T-cell epitope on the circumsporozoite protein of P. vivax.